2016
DOI: 10.20524/aog.2016.0056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors affecting patient responses to pancreatic cancer treatment

Abstract: Cancer of the exocrine pancreas is a malignancy with a high lethal rate. Surgical resection is the only possible curative mode of treatment. Metastatic pancreatic cancer is incurable with modest results from the current treatment options. New genomic information could prove treatment efficacy. An independent review of PubMed and ScienceDirect databases was performed up to March 2016, using combinations of terms such pancreatic exocrine cancer, chemotherapy, genomic profile, pancreatic cancer pharmacogenomics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…However, because of its late diagnosis, surgery is a viable option to less than 20% of cases [5]. Chemotherapy drugs for PaCa include gemcitabine, 5-fluorouracil, cisplatin, and paclitaxel [6, 7]. These cytotoxic therapies have a number of negative side effects including low blood count and peripheral neuropathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its late diagnosis, surgery is a viable option to less than 20% of cases [5]. Chemotherapy drugs for PaCa include gemcitabine, 5-fluorouracil, cisplatin, and paclitaxel [6, 7]. These cytotoxic therapies have a number of negative side effects including low blood count and peripheral neuropathy [8].…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Previous studies have demonstrated that mutations in different genes such as K‐RAS, hENT1, DCK, CDA, HMLH1, TP1DPD, HER2 and SMAD4, could drive the development of PC chemoresistance. 7 However, the identified genetic alterations cannot fully explain the chemoresistance observed in PC and mounting data suggested that non‐genetic mechanisms, including microRNAs (miRNAs) and circular RNAs (circRNAs), are also implicated in chemoresistance development and treatment response. 8 For instance, increasing number of circRNAs have been involved in PC chemoresistance through high‐throughput sequencing studies.…”
Section: Introductionmentioning
confidence: 99%
“…The complicated aetiology of PC tumorigenesis and chemoresistance has been revealed through the application of next‐generation sequencing technology 5,6 . Previous studies have demonstrated that mutations in different genes such as K‐RAS, hENT1, DCK, CDA, HMLH1, TP1DPD, HER2 and SMAD4, could drive the development of PC chemoresistance 7 . However, the identified genetic alterations cannot fully explain the chemoresistance observed in PC and mounting data suggested that non‐genetic mechanisms, including microRNAs (miRNAs) and circular RNAs (circRNAs), are also implicated in chemoresistance development and treatment response 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The detection of DNA fragments with specific sequences has applications in the diagnosis of infectious diseases (1) and genetic diseases, (2) as well as in precision medicine. (3) In the case of genetic diseases, early diagnosis allows prompt medical treatment before disease progression. (4) Genetic diagnosis has become increasingly important, as it helps to prevent the onset of disease before occurrence.…”
Section: Introductionmentioning
confidence: 99%